Sweet Tassa: Music of the Indian Caribbean Diaspora - Ballengee, Christopher L (Journal of Anthropological Films, 2022)
Sweet Tassa: Music of the Indian Caribbean Diaspora details the history, repertoire, and socio-political significance of tassa drumming in Trinidad & Tobago. The film profiles the life and work of noted tassa drummer Lenny Kumar and his family while also developing the notion of tassa performance practice as a metaphor for Indian Trinidadian cultural and national identity. In the process, the film traces tassa’s movement from India to the Caribbean, summarizes its transformation in diaspora, and speculates about its future. Proceeding from analysis of tassa repertoire in Muslim and Hindu performance contexts, the film explores tassa’s physical and conceptual transformations in diaspora and the ongoing push to make tassa a co-national instrument alongside steel pan. In this regard, interviewees discuss the implication of tassa as “foreign”—despite more than 150 years of Indian presence in the Caribbean—and therefore unsuitable as a co-national instrument alongside steel pan. The film’s conclusion emphasizes tassa as an encapsulation of Indian identity: tassa’s performance contexts and performance practice signal India as a place of origin. Yet these very same aspects, by virtue of their persistence in diaspora, equally signal Trinidad and Tobago as home.